A Novel Hydrogen Sulfide Donor Reduces Pilocarpine-Induced Status Epilepticus and Regulates Microglial Inflammatory Profile - Zhongrui Liu (Frontiers Media S.A., 2021)
Although epilepsy is one of the most common neurologic disorders, there is still a lack of effective therapeutic drugs for it. Recently, we synthesized a novel hydrogen sulfide (H2S) donor, which is found to reduce seizures in animal models effectively. But it remains to be determined for its mechanism. In the present study, we found that the novel H2S donor could reduce pilocarpine-induced seizures in mice. It alleviated the epileptic behavior, the hippocampal electroencephalography (EEG) activity of seizures, and the damage of hippocampal neurons in status epilepticus mice. In addition, the novel H2S donor could reduce microglial inflammatory response. It not only reduced the upregulation of pro-inflammatory markers [inducible nitric oxide synthase (iNOS) and cyclooxygenase 2 (COX2)] in status epilepticus mice, but also increased the levels of microglial anti-inflammatory marker arginase-1 (Arg-1). In lipopolysaccharide-treated microglia BV2 cells, administration of the H2S donor also significantly reduced the lipopolysaccharide-induced upregulation of the expression of the pro-inflammatory markers and increased the expression of the anti-inflammatory markers. Thus, the novel H2S donor regulates microglial inflammatory profile in status epilepticus mice and in vitro. These results suggested that the novel H2S donor can reduce seizures and regulate microglial inflammatory profile, which may be a novel mechanism and potential therapeutic strategy of the H2S donor anti-seizures.